Two New Species of Pseudopaludicola Miranda-Ribeiro, 1926 (Anura: Leptodactylidae: Leiuperinae) from Eastern Bolivia and Western Brazil - Pansonato, André [UNESP]; Veiga-Menoncello, Ana Cristina P.; Mudrek, Jessica R.; Jansen, Martin; Recco-Pimentel, Shirlei M.; Martins, Itamar A. [UNESP]; Strüssmann, Christine (My University, 2016)
Two new species of Pseudopaludicola from midwestern Brazil are described. One of them, distributed in Bolivian and Brazilian areas within the Upper Paraguay and Upper Guaporé river basins, is characterized by the presence of a conspicuous conical tubercle on each heel, by T-shaped terminal phalanges, and so belongs to the formally recognized Pseudopaludicola pusilla group. The advertisement call is composed of a series of 14-720 notes with concatenated pulses-each lasting for 5-25 ms-and mean dominant frequency of 5071 ± 242 Hz. The second species, restricted to the southeastern-most region of the Brazilian state of Mato Grosso, is characterized mainly by a 2n = 18 karyotype, an advertisement call composed of series of 12-287 notes with concatenated pulses and mean dominant frequency of 4167.7 ± 287.5 Hz. A detailed description of the karyotype of this latter species is also provided.
Keywords: Advertisement call; Amphibia; Cytogenetics; Swamp frogs; Taxonomy